2021
DOI: 10.1002/slct.202004531
|View full text |Cite|
|
Sign up to set email alerts
|

A New Fluorescence MOF for Highly Sensitive Detection of Acetylacetone

Abstract: A novel metal‐organic framework (MOF) assembled by a semi‐rigid tricarboxylate, namely, 5‐(3,4‐dicarboxylphenoxy) nicotic acid (H3L) has been solvothermally synthesized: [Zn3(L)2(H2O)2] ⋅ 3H2O 1. Single‐crystal X‐ray diffraction analysis indicates that MOF 1 shows 2‐D layer with quadrangle channels along the a axis (ca. 7.0×8.3 Å2). The 2‐D layer self‐assembles into a final 3‐D supramolecular network via the interlayer π⋯π interactions. The photoluminescence investigations indicate that 1 can selectively and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Hazardous solvents, highly toxic substances that can cause cancer, deformities, and blood poisoning, generally include toxic organic solvents and amine-based organic molecules [ 136 , 137 ]. Up to now, several methods such as high performance liquid chromatography, nuclear magnetic resonance spectroscopy, mass spectrometry, and infrared and ultraviolet (UV) spectroscopy have been available for probing hazardous solvents.…”
Section: Lmofs For Hazardous Materials Detectingmentioning
confidence: 99%
“…Hazardous solvents, highly toxic substances that can cause cancer, deformities, and blood poisoning, generally include toxic organic solvents and amine-based organic molecules [ 136 , 137 ]. Up to now, several methods such as high performance liquid chromatography, nuclear magnetic resonance spectroscopy, mass spectrometry, and infrared and ultraviolet (UV) spectroscopy have been available for probing hazardous solvents.…”
Section: Lmofs For Hazardous Materials Detectingmentioning
confidence: 99%
“…Electrons in the BBZB molecular orbital (HOMO) may be excited to its lowest unoccupied molecular orbital (LUMO), which can subsequently be transferred to the LUMO of acac, SA, or BZ. The comparison reveals that the LUMO energy level of BBZB (−0.16 eV) 45 is significantly higher than those of acac (−2.36 eV), 46 SA (−1.78 eV), and BZ (−1.90 eV), 47 supporting electron transfer from BBZB to acac, SA, and BZ. Therefore, it can be concluded that the cause of fluorescence quenching of JXUST-33 is the PET process and competitive energy absorption of acac, SA, or BZ.…”
Section: ■ Introductionmentioning
confidence: 92%
“…In addition, the nucleobases are highly conjugated planar molecules and contain N, O and H atoms, which can exhibit weaker interactions such as p-p stacking or hydrogen bonding with the ligand moiety of Cobpy. [44][45][46] As Co-bpy is evenly dispersed in water that favors the accumulation of nucleobase molecules on and near the easily accessible surface of the MOF, thus these weaker interactions are possible, which may also affect the electron transfer path of the MOF in some way, promoting fluorescence quenching. 26 In addition, to comprehend the type of quenching, i.e., static or dynamic, fluorescence lifetime measurements using the TCSPC (time-correlated single-photon counting) method were carried out (Fig.…”
Section: Mechanistic Insight Into the Sensingmentioning
confidence: 99%